2007
DOI: 10.1080/08037050701343688
|View full text |Cite
|
Sign up to set email alerts
|

Large and small artery endothelial function in patients with essential hypertension – Effect of ACE inhibition and beta‐blockade

Abstract: Hypertension has been associated with changes in endothelial function in both large muscular arteries and small resistance arteries. We evaluated the relationship between blood flow velocity and dilatation of the brachial artery following transient forearm ischemia and acetylcholine-induced relaxation in subcutaneous small arteries and the influence of antihypertensive therapy on both in patients with essential hypertension. Thirty-one previously untreated hypertensive patients were randomized in a double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This was a homogeneous population without known risk factors. In reality, patients with chronic diseases would be on medications, some of which have antiinflammatory effects (Buus et al, 2007;Mäki-Petäjä et al, 2007). Further studies need to be performed on such subjects to observe any possible coffeedisease interaction on endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…This was a homogeneous population without known risk factors. In reality, patients with chronic diseases would be on medications, some of which have antiinflammatory effects (Buus et al, 2007;Mäki-Petäjä et al, 2007). Further studies need to be performed on such subjects to observe any possible coffeedisease interaction on endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…34 No difference between medications was observed. The increase in the percentage of dilation after 1 year of treatment was inversely correlated with change with treatment in the rCBF response during working memory in all of the ROIs (r: Ϫ0.50 to Ϫ0.68; PՅ0.01).…”
Section: Peripheral Vasodilative Effectsmentioning
confidence: 94%
“…23 Accordingly, increased ATII concentrations, along with increased levels of superoxide anions, have been shown in the shoulder region of atherosclerotic plaques. 67 In line with a role of ATII in endothelial dysfunction and hypertension, numerous studies have now demonstrated that the therapy with angiotensin-converting enzyme inhibitors and AT-1 receptor blockers is associated with an improvements in endothelial responsiveness [68][69][70][71][72] (the existence of negative reports also needs to be acknowledged). 73 In animal models of ATII-induced hypertension, 14 increased ROS production by Nox was also associated with eNOS uncoupling.…”
Section: Ros Sources In Hypertension Nadph Oxidasesmentioning
confidence: 98%